Are genetic drift and stem cell adherence in laboratory culture issues for cultivated meat production? - Jaime-Rodríguez, Manuel; Cadena-Hernández, Ana Laura; Rosales-Valencia, Lorena Denisee; Padilla-Sánchez, Juan Miguel; Chavez-Santoscoy, Rocio Alejandra (Frontiers in Nutrition, 2023)
Mesenchymal stem cell-based cultivated meat is a promising solution to the ecological and ethical problems posed by traditional meat production, since it exhibits a protein content and composition that is more comparable to original meat proteins than any other source of cultivated meat products, including plants, bacteria, and fungi. Nonetheless, the nature and laboratory behavior of mesenchymal stem cells pose two significant challenges for large-scale production: genetic drift and adherent growth in culture. Culture conditions used in the laboratory expose the cells to a selective pressure that causes genetic drift, which may give rise to oncogene activation and the loss of “stemness”. This is why genetic and functional analysis of the cells during culture is required to determine the maximum number of passages within the laboratory where no significant mutations or loss of function are detected. Moreover, the adherent growth of mesenchymal stem cells can be an obstacle for their large-scale production since volume to surface ratio is limited for high volume containers. Multi-tray systems, roller bottles, and microcarriers have been proposed as potential solutions to scale-up the production of adherent cells required for cultivated meat. The most promising solutions for the safety problems and large-scale obstacles for cultivated meat production are the determination of a limit number of passages based on a genetic analysis and the use of microcarriers from edible materials to maximize the volume to surface proportion and decrease the downstream operations needed for cultivated meat production.